Internal party democracy and party institutionalization in Nigeria: implication for democratic consolidation-1999-2015 - Innocent, Alfa Patrick (2019)
The study interrogates the interface between internal party democracy, party institutionalization and democratic consolidation in Nigeria's Fourth Republic. It is a conceptual and qualitative study which employed primary and secondary data collection procedures. The data were analysed thematically. The study contends that since Nigeria's return to democratic rule on May 29, 1999, political parties have not been able to contribute meaningfully to democratic consolidation. Using two leading Fourth Republic political parties, the People Democratic Party (PDP) and the All Progressives Congress (APC) as case studies, the study posits that the inability of the parties to make a positive impact in consolidating the country's democracy is informed by their level of institutionalization which have been undermined by the dearth of internal party democracy. This has manifested in the dysfunctional ways in which they evolve, their inherent lack of unity and focus, involvement in electoral fraud, intergovernmental disharmony, political violence, ideological deficit, indiscipline, elite polarisation and endemic defection. The study avers that there is a critical need for Nigeria's political parties to, among others, adhere to the tenets of internal party democracy, hinge their formation and operations on ideologies, refrain from ethnic politics and remain stable with effective societal roots at all times. The study also advocates the need to evolve a nationalistic and visionary leadership. The need for an articulate political socialization is also seen by the study as imperative in order to promote the values of unity, hard work, accommodation and discipline. The INEC should be constitutionally empowered to enforce internal party democracy. Efficient intraparty and interparty deliberations are also prescriptive to entrench the culture of cooperation. Fundamentally too, the study suggests that a new political culture and legal framework should be pursued by relevant institutions to ensure that political competitions are anchored on constitutional government, separation of powers and the rule of law. The study concludes that the enforcement of these recommendations by the relevant stakeholders will promote internal party democracy, facilitate party institutionalization and fast track democratic consolidation in Nigeria's Fourth Republic.